Pemanfaatan Bonggol Pisang Sebagai Bioaktivator dalam Proses Pengomposan Limbah Sekam Padi di Penggilingan Padi Desa Pelabuhan Dalam Ogan Ilir - Zairinayati; Ilza Aprilia (jurnal kesehatan terapan sains dan teknologi, 2023)
Composting is a method of organic waste management that aims to reduce and change the composition of waste into useful products. Composting naturally takes 2-6 months so it is necessary to use a bioactivator to speed up the decomposition process. This study used a banana weevil bioactivator as a source of local microorganisms because the nutritional content in banana weevil is a food source so that microbes develop well. The aim of the study was to determine the effectiveness of the banana weevil bioactivator in the composting process of rice husk waste at the rice mill in Pelabuhan Dalam Village, Pemulutan Ogan Ilir District. This research was conducted from April to June 2023. The research design used a descriptive method, by observing the changes in the rice husk waste compost until it was ripe including several concentrations of the banana weevil bioactivator used, namely 50 ml, 60 ml, 70 ml, 80 ml, 90 ml and 100 ml. as well as temperature, humidity, and color control. The results showed that the composting time required was 31 days, the average temperature with 5 concentrations was 33.4%, the average humidity was 43% and the color of the compost at a concentration of 100 ml was blackish brown. The conclusion is that the temperature is very supportive, starting from 30-38 °C the humidity ranges from 40-60% with regular turning and watering, the color of rice husk is yellow and after the addition of banana weevil bioactivator during the composting process the color changes to blackish brown.